Innovation project management : methods, case studies, and tools for managing innovation projects - Kerzner, Harold (Hoboken, New Jersey : John Wiley & Sons, Inc., 2019)
"Harold Kerzner has bridged innovation, project management, and strategic planning in Innovation Project Management to offer students and practicing professionals the tools, processes, and metrics needed to successfully manage innovation projects. By analyzing innovation from all sides, this compendium of innovation project management breaks down traditional project management methods and explains why and how innovation projects should be managed differently. This title includes exclusive insights from world-class organizations such as Airbus, Boeing, Deloitte, Hitachi, IBM, Siemens, and more. This is a must-have title for practicing project managers, as well as students in project management, innovation, and entrepreneurship programs. Each case study contains questions for discussion, and Instructors have access to extensive PowerPoint lecture slides by chapter and an Instructors Manual via the book's companion website"--
Introduction to innovation project management -- Types of innovation -- Innovation and strategic planning -- Innovation tools and processes -- From traditional to innovation project management thinking -- Innovation management software -- Value-based innovation project management metrics -- Business models -- Disruptive innovation -- Innovation roadblocks -- Defining innovation success and failure -- Innovation in action -- Case Studies.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Technological innovations -- Management; Project management; Innovations -- Gestion; Gestion de projet; BUSINESS & ECONOMICS / Project Management; Project management; Technological innovations -- Management; Projektmanagement